PENERAPAN PEMBELAJARAN AKTIF BERBASIS EKSPLORASI DENGAN PENDEKATAN PROSES SAINS UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SDN 246 BULU-BULU KABUPATEN BONE - Rosmalah; Sitti Jauhar; Anisa (MACCA : Science-Edu Journal, 2026)
This study aims to improve students’ learning outcomes in Natural and Social Sciences (IPAS) through the implementation of active learning based on exploration with a science process approach in fifth-grade students of SDN 246 Bulu-Bulu, Bone Regency. This research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 17 students. Data were collected through observation, tests, and documentation, and analyzed qualitatively through data reduction, data display, and conclusion drawing. The results showed that the implementation of exploration-based active learning with a science process approach improved students’ IPAS learning outcomes. In the first cycle, both teacher and student activities were categorized as fair to good, although several limitations were still found, particularly in student participation. In the second cycle, there was a significant improvement in both learning activities and student outcomes, with most students achieving the minimum mastery criteria. Therefore, it can be concluded that exploration-based active learning with a science process approach is effective in improving elementary school students’ learning outcomes in IPAS.